Effectiveness of the Structured Teaching Programme on Water Conservation Methods among School Children at a Selected Private School, Coimbatore - Kavitha Vadamalraj; Fairoj Banu Abdullah; Gokila Devi Pandiyaraj; Goutham Prasad; Helna Rose Sabu; Irene Sara Peter (Scientia Publica Media, 2025)
Water conservation has emerged as a critical global concern owing to rising demand, rapid population growth, urban expansion, and climate change impacts. India is particularly vulnerable, with many regions experiencing frequent water shortages, which underscores the role of education as a key approach for sustainable resource management. Within the framework of Education for Sustainable Development (ESD), it is essential to equip young learners with environmental knowledge, positive attitudes, and practical skills that foster responsible behaviours. The present study was undertaken to examine the effectiveness of a structured teaching programme (STP) on water conservation among school children. A pre-experimental one-group pre-test and post-test research design was employed with 100 students aged 14–16 years, purposively chosen from classes IX to X in a private school in Coimbatore. Data collection was carried out using a validated knowledge, attitude, and practice (KAP) tool comprising 15 multiple-choice questions to assess knowledge, 10 attitude statements, and 10 practice-related items scored on a five-point Likert scale. The intervention involved structured teaching sessions that combined interactive discussions, visual aids, and activity-based learning strategies. Statistical analysis was performed using SPSS version 26.0 with descriptive measures and paired t-tests. The findings demonstrated significant improvement across all domains. Knowledge scores rose from 7.5 to 12.8, attitude scores from 30.1 to 41.7, and practice-related awareness from 5.9 to 9.1, with all differences statistically significant at p < 0.001. Furthermore, 86% of students achieved knowledge scores above 10 after the programme, indicating effective knowledge acquisition. In summary, the study highlights that structured teaching is a valuable approach for enhancing awareness of water conservation in school settings. Embedding such interventions into the school curriculum can play an important role in advancing environmental sustainability and encouraging long-term behavioural change.